Integrating mental health care into home‐based nursing services: A qualitative study utilising normalisation process theory. Issue 9 (26th July 2021) - Ohlsen, Sally; Sanders, Tom; Connell, Janice; Wood, Emily
Abstract: Aims and objectives: To identify barriers and facilitators to implementing community nurses being trained as psychological wellbeing practitioners and integrating this practice into home‐based primary care nursing, through key stakeholders' perceptions. Background: Current drivers in UK primary care aim to increase access to mental health services and treatment, to achieve parity of esteem between physical and mental health care for patients who are housebound. However, there remains limited evidence on how to successfully implement this. Training community nurses as psychological wellbeing practitioners to offer mental health care alongside their current home‐based services is one option. Design: A pluralistic qualitative study. This study followed the COREQ checklist for reporting qualitative research. Methods: Twenty key stakeholders were purposively recruited and interviewed including twelve health professionals and eight patients. Semi‐structured interviews were analysed using a theoretical thematic analysis informed by normalisation process theory concepts of coherence, cognitive participation, collective action and reflexive monitoring, to explore the barriers and facilitators to implementation. Results: Staff and patients reported high coherence and cognitive participation, valuing the integrated roles. Facilitators included the development of clearer referral pathways and increased mental health knowledge in the wider team. However, sustainability and current siloed healthcare systems were identified as barriers to implementation. Conclusions: A key obstacle to long‐term implementation was the practical structures and financial boundaries of siloed healthcare systems, making long‐term sustainability unviable. Relevance to clinical practice: Community nurses with additional mental health training can integrate these skills in practice and are valued by their team and patients offering holistic care to patients within their home and informal knowledge transfer to the wider team. However, long‐term sustainability is required if this is to be adopted routinely. Further evidence is needed to better understand the positive outcomes to patients and potential cost savings.